Expression and clinical significance of short-chain fatty acids in pregnancy complications - Chen, Siqian; Li, Jialin; Ren, Shuaijun; Gao, Yajie; Zhou, Yuping; Xuan, Rongrong (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: To investigate the expression of short-chain fatty acids (SCFAs)—metabolites of intestinal flora—in gestational complications of gestational diabetes mellitus (GDM), preeclampsia (PE), and intrahepatic cholestasis of pregnancy (ICP), and its clinical significance. Methods: Targeted metabonomics was used to detect SCFAs in the serum of 28 GDM pregnant women, 28 PE pregnant women, 29 ICP pregnant women, and 27 healthy pregnant women (NP); their expression changes were observed; the correlation between SCFAs and clinical characteristics was studied; and their potential as biomarkers for clinical diagnosis was evaluated. Results: There were significant differences in the SCFA metabolic spectrum between the GDM, PE, ICP, and NP groups. Quantitative analysis showed that the content of isobutyric acid in the three pregnancy complications groups (the GDM, PE, and ICP groups) was significantly higher than that in the NP group (p < 0.05), and other SCFAs also showed significant differences in the three pregnancy complications groups compared with the NP group (p < 0.05). Receiver operating characteristic (ROC) curve analysis of the generalized linear model showed that multiple SCFAs were highly sensitive and specific as diagnostic markers in the pregnancy complications groups, where isobutyric acid was highly predictive in GDM (area under the ROC curve (AUC) = 0.764) and PE (AUC = 1), and caproic acid was highly predictive in ICP (AUC = 0.968), with potential clinical application. Conclusion: The metabolic products of intestinal flora, SCFAs, during pregnancy are closely related to pregnancy complications (GDM, PE, and ICP), and SCFAs can be used as potential markers of pregnancy complications.